The relationship between food insecurity and objective and subjective income indicators in Poland - Dudek, Hanna (Zależność między brakiem bezpieczeństwa żywnościowego a obiektywną i subiektywną sytuacją dochodową: wyniki dla Polski, 2020)
The study analyses food insecurity in Poland on the basis of data from the Food and Agriculture Organization of the United Nations. This data assesses the scale of experiencing food insecurity by the respondents. It includes information obtained during 2014-2019 from 6080 people. The dependence of food insecurity on the subjective and objective income situation of individuals was examined. Typical methods of analysis were used, such as Pearson’s χ2 test, Cramer V and Kendall τb measures, and the logit model. It was found that the perception of food insecurity depends more on the subjective rather than objective income situation
Śląski Przegląd Statystyczny = Silesian Statistical Review, 2020, Nr 18 (24), s. 121-132